Comparison of different methods for obtaining centric relation: a systematic review - De Moraes Melo Neto, Clóvis Lamartine [UNESP]; Da Silva, Emily Vivianne Freitas [UNESP]; De Sousa Ervolino, Isabela Caroline [UNESP]; Dos Santos, Daniela Micheline [UNESP]; De Magalhães Bertoz, André Pinheiro [UNESP]; Goiato, Marcelo Coelho [UNESP] (My University, 2021)
The objective of this study was to compare techniques of different methods of obtaining centric relation to verify which technique generates the greatest reproducibility of the centric relation. The PubMed/MEDLINE, Cochrane Library, SciELO, Scopus, and Web of Science databases were searched for articles published up to May 15, 2018. The search terms were combinations of dental centric relationwith each of the following terms (individually): reproducibility of findings; jaw relation record; chin point; gothic arch; bimanual manipulation; swallowing; and jig.The inclusion criteria included clinical studies in English that had to compare at least 2 techniques representing different methods for obtaining centric relation (based on the reproducibility of the centric relation) in individuals without temporomandibular dysfunction; and studies performed in individuals with complete or nearly complete dentition or complete edentulism. Methods (techniques) included in this study were guided methods (chin point guidance and bimanual manipulation); graphic methods (intraoral and extraoral gothic arch tracing); and physiologic methods (swallowing and tongue retrusion along the palate). A total of 1638 articles were identified. After the inclusion and exclusion criteria were applied, 7 articles were included in this review. None of the reviewed studies evaluated edentulous individuals. Two articles compared physiologic methods with guided methods; one concluded that the swallowing technique generates greater variability than guided methods, and the other concluded that there was no difference between the swallowing technique and chin point guidance. Of 5 articles comparing intraoral gothic arch tracing with guided methods, 2 showed similar results between different methods, 2 showed superior results for gothic arch tracing, and 1 showed superior results for the guided methods. Based on the guided methods and swallowing technique, it is not possible to conclude which technique can generate the greatest reproducibility of the centric relation. It is possible to suggest that in most cases intraoral gothic arch tracing is superior or equivalent when compared to guided methods.
Keywords: dental centric relation; jaw relation record; reproducibility of findings